Optimization Photodegradation of Methylene Blue Dye using Bentonite/PDA/Fe3O4@CuO Composite by Response Surface Methodology - Riyanti, Fahma; Hariani, Poedji Loekitowati; Hasanudin, Hasanudin; Rachmat, Addy; Purwaningrum, Widia (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
This study aims to synthesize bentonite/PDA/Fe3O4@CuO composites as a catalyst for the photodegradation of Methylene blue dye. Composite characterization involves X-ray Diffractometry (XRD), Scanning Electron Microscopy (SEM) with X-ray Energy Dispersion Spectrometry (EDS), UV-Vis Diffuse Reflectance Spectroscopy (UV-Vis DRS), and Vibrating Sample Magnetometer (VSM). Response Surface Methodology (RSM) employs Central Composite Design (CCD) to optimize photodegradation by varying dye concentration, irradiation time, and catalyst dose. The bentonite/PDA/Fe3O4@CuO composites exhibit a saturation magnetization value of 54.82 emu/g and a band gap of 2.1 eV. The optimization revealed that concentration and dose significantly impact the photodegradation efficiency. A quadratic model is suitable for modeling the photodegradation of Methylene blue dye using bentonite/PDA/Fe3O4@CuO composites, as determined by analysis of variance (ANOVA). The optimal conditions for achieving maximum photodegradation efficiency were identified as a dye concentration of 10 mg/L, an exposure time of 90 min, and a catalyst dose of 1.67 g/L. Under these parameters, the photodegradation process exhibited a remarkable efficiency of 100%. The Bentonite/PDA/Fe3O4@CuO composites exhibited strong stability, efficiency, and recyclability. After six photodegradation cycles, there was a 5.18% decrease in photodegradation efficiency. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).